Attitudes towards Chagas' disease in an endemic Brazilian community - Sarah Williams-Blangero; John L. VandeBerg; Antonio R. L. Teixeira
Chagas' disease remains a major public health concern throughout much of Latin America. In Brazil, segments of the population experience Trypanosoma cruzi infection rates as high as 65%, indicating that control programs are still needed. Few data are available concerning people's health beliefs related to Chagas' disease in heavily infected populations. Such health beliefs may significantly impact the effectiveness of intervention schemes. The purpose of this study was to assess health beliefs related to Chagas' disease in a population experiencing high infection rates with the causal parasite. The focal population for the study consisted of the residents of Posse, a rural community in the State of Goiás. The results indicate that a majority of the population had a high degree of knowledge about Chagas' disease and the vector involved in its transmission. These findings indicate that control programs conducted by the Brazilian Ministry of Health have included effective educational components.